Gender differences in elementary school students’ fraction learning: roles of spatial ability and mathematical anxiety - Zhang, Ruhai; Chen, Zhongting; Deng, Ciping (Frontiers in Psychology, 2024)
Aim: In this study, we examined gender differences in fraction learning and explored potential underlying mechanisms. Methods: The mediating effects of spatial ability and mathematical anxiety on gender differences in fraction learning were tested in elementary school students. A total of 165 sixth-grade students (83 girls) from public elementary schools participated in the study. All participants completed a series of tasks, including a mathematical anxiety test, two spatial ability tasks (spatial working memory and mental rotation tests), and a fraction knowledge test (incorporating fraction arithmetic, fraction number line, and fraction concept knowledge). Results: Significant gender differences exist in student performance in terms of fractional arithmetic, fractional number line estimation, mathematical anxiety, and spatial working memory. We also identified a chain-mediating effect of spatial working memory and mathematical anxiety on the relationship between gender and fractional arithmetic. Conclusions: The findings suggest a developmental pathway linking gender differences in spatial cognition to fraction learning, contributing to a better understanding of the cognitive and affective factors underlying gender differences in fraction learning during early adolescence. Furthermore, there are several practical implications for reducing gender differences in mathematics education during school years.